Потенціал геоінформаційних технологій у вирішенні проблем екологічної безпеки водних об'єктів - Трофимчук, О.М.; Триснюк, В.М. (Екологічна безпека та природокористування, 2012)
Urgency ofthe problemof ecological safetyof natural andman-caused increase ingeo systems antropogresiyi, expanding the range and increasing gintensity of dangerous sprocesses anddecrease the stability of geosystems. Advanced Applicationsof GISdue to their possibleuse as a deployment environment of static and dynamic models that illustrate a variety of natural and socioeconomic processes and functional relation ships.